EFEKTIVITAS HUKUM PIDANA PADA PENYELESAIAN MEDIASI ANTARA TERSANGKA DENGAN KORBAN DALAM KASUSPENCEMARAN NAMA BAIK - Tuti Hutagalung; Lesson Sihotang (JOURNAL OF LAW AND NATION, 2025)
Usually, the resolution of criminal cases for the parties involved often takes place through a litigation process. However, nowadays, the parties involved must be introduced to the method of resolving cases by resolving cases through mediation. As with defamation cases, it would be best to resolve the matter between the victim and the perpetrator using mediation which can be used as an alternative solution. Mediation as an alternative for resolving minor criminal cases outside of court by bringing together perpetrators and victims of crime directly changes the perspective of criminal law which is known to be static in resolving disputes with processes and procedures that remain towards humanistic criminal law, because mediation's main focus is peace, not peace. revenge. The purpose of writing this journal is to find out the extent of the effectiveness of criminal law in resolving criminal defamation cases using the mediation method (penal mediation). Through normative juridical analysis methods, this journal assesses the benefits and obstacles of mediation in defamation cases in Indonesia, especially in the context of the effectiveness of Criminal Law